The role of nutrition as risk factor for polyneuropathy: a case‐control study. Issue 4 (31st August 2017) - Visser, Nora A.; Notermans, Nicolette C.; de Vries, Jeanne H. M.; van den Berg, Leonard H.; Vrancken, Alexander F. J. E.
Abstract: The aim of this case–control study is to investigate the role of nutrition as risk factor for polyneuropathy. Three hundred eighteen patients with chronic idiopathic axonal polyneuropathy and 636 matched controls completed a validated food frequency questionnaire that covered nutrient intake and alcohol consumption. As risk estimates, we calculated adjusted odds ratios for the intake of energy and nutrients. Energy and nutrient intake did not differ between patients and controls, regardless of moderate alcohol consumption. Nutrition is not a risk factor for chronic idiopathic axonal polyneuropathy.